Systemic bleeding including pulmonary haemorrhage following hump-nosed pit viper (Hypnale hypnale) envenoming: A case report from Sri Lanka. (December 2019) - Rathnayaka, R.M.M.K. Namal; Ranathunga, P.E.A.Nishanthi; Kularatne, S.A.M.
Abstract: Out of seven venomous land snake species of Sri Lanka, hump-nosed pit viper ( Hypnale spp. ) causes the commonest venomous snakebites. It is widely distributed all over the country except in the peninsula of Jaffna. The genus has three species naming H. hypnale, H. zara and H. nepa . They frequently cause local envenoming and rarely cause coagulopathy and acute kidney injury. Systemic bleeding is the most trivial complication associated with coagulopathy caused by these snakes and pulmonary haemorrhages are one of them which are rarely reported. Antivenoms are currently not available for genus Hypnale bites in Sri Lanka. We describe a fatal case of pulmonary haemorrhage caused by a proven hump-nosed viper ( Hypnale hypnale ) bite associated with other systemic bleeding manifestations and thrombotic microangiopathy. This is the first known case of pulmonary and intracranial haemorrhages caused by hump-nosed viper bite. Highlights: Systemic bleeding following hump-nosed viper ( H.hypnale ) bite is described. Pulmonary haemorrhage is the most trivial manifestation. Unavailability of antivenoms for these bites in Sri Lanka is highlighted. Complex nature of Hypnale venom is clinically explained.